Preoperative Transurethral Contrast‐Enhanced Ultrasonography in the Diagnosis of Female Urethral Diverticula. (24th April 2018) - Wang, Xia; Dou, Chaoran; Yan, Yulin; Song, Lujie; Hu, Bing; Ying, Tao
Abstract : Objectives: To explore the value of transurethral contrast‐enhanced ultrasonography (CEUS) in the diagnosis and evaluation of female urethral diverticula. Methods: This study prospectively enrolled 35 women with periurethral cystic lesions, who underwent preoperative transurethral CEUS at our single center between April 2015 and May 2017. The diagnosis of a urethral diverticulum was made by the detection of microbubbles inside the lesion. Data regarding the structure and ostia of the diverticula were collected and then compared with intraoperative findings. Results: The median (interquartile range) age of the 35 patients was 43 (34–48) years. The most common manifestations were dysuria (43%) and palpable masses (40%). On transurethral CEUS, 20 patients were found to have urethral diverticula. The diverticula involved the proximal, mid, and distal urethra with different sizes. The shapes of the diverticula were simple in 4 patients (20%), U shaped in 8 patients (40%), and circumferential in 8 patients (40%). A total of 23 ostia were identified. Seventeen women (85%) had 1 ostium, and 3 women (15%) had 2 ostia. Twenty‐one diverticular ostia (91%) were located from the 3‐ to 9‐o'clock positions. The median (interquartile range) distance from the diverticular ostia to the bladder neck was 20 (9–31) mm. During surgery, all US presentations correlated well with surgical findings, and 21 patients were confirmed to have urethral diverticula. The transurethral CEUS had sensitivity of 95% and specificity of 100%. Conclusions: Transurethral CEUS is an effective method for identifying the structure and ostium of female urethral diverticula. It may have a potential role in preoperative planning and surgical management.